EFFECT OF DURATION OF ZnO PROTOTOTYPE DYE SENSITIZED SOLAR CELL LAYERS OF FAMBIR (UNCARIA) FRUIT EXTRACT AS A PHOTOSENSITIZER - Rahmatun Rahma Toyyibah; Abdul Rais (Universitas Negeri Medan, 2026)
DSSC research using organic dyes has been carried out by fabricating solar cells using dyes from gambir plants. The stages of this research are the manufacture of gambir fruit dye as a photosensitizer. This study aims to determine the effect of DSSC performance due to variations in soaking time. XRD test results show crystal sizes of 28.44536 nm, 7.66144 nm, 8.3061 nm, 2.93336 nm, and 19.97532 nm. SEM characterization of the ZnO layer on FTO glass looks uneven due to the difficulty of regulating the stability of the layer using the Doctor Blade method. UV-Vis characterization with a wavelength of 200-800 nm shows the results that the dye solution can work in invisible light to visible light with an absorbance value of 5.254 a.u. The current and voltage values in the immersion variation will be accumulated to determine the efficiency value of the DSSC. The efficiency values for 14 hours, 16 hours, and 18 hours are 0.0146%, 0.0192% and 0.0692%.